“Satu Tujuan Tinggi Untuk Dicapai”: Sebuah Tulisan Ellen White bagi Generasi Muda - Kasingku, Juwinner; Priscilla Kasingku, Blessy (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study is a descriptive qualitative research. Where to discuss a famous piece of literature by Ellen White challenging young people to adhere to the principles present-day life and the life promised by God in the beyond. According to this study, young people need to have noble dreams, be able to carry the light of Christ, have a wide range of desires, and become soldiers of Christ—that is, actively participate in serving God. The steps to achieve high and noble goals are written in this article. Thus, the young people can ultimately achieve both the lofty and noble goals of life in this world and of the much greater life that God will bestow.